2023
DOI: 10.22540/jfsf-08-032
|View full text |Cite
|
Sign up to set email alerts
|

Risk of sarcopenia, fear of COVID-19, anxiety, depression and physical activity levels: Associations across patients on hemodialysis within Greece

Abstract: Objectives: The purpose of this multicenter cross-sectional study was to investigate the association between SARC-F, fear of COVID 19, anxiety, depression and physical activity in patients undergoing hemodialysis. Methods: This study was conducted in 3 hemodialysis centers in Greece during the period of the COVID-19 pandemic. Sarcopenia risk was assessed using the Greek version of SARC-F (≥4). Demographic and medical history were collected from the patient’s medical cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…It is important to emphasize that, according to the literature review, there are no reports focusing directly on the analysis of physical activity using IPAQ in the context of VR utilization among haemodialysis patients. Studies conducted in haemodialysis patient groups used IPAQ only to determine the relationship between the level of physical activity and the occurrence of sarcopenia [28], cognitive abilities [29], depression [30], cardiovascular disorders [31], and to compare the short version of the IPAQ with accelerometer-based physical activity measurement in haemodialysis patients [32], as well as to assess the plasma levels of 25-hydroxyvitamin D compared to the level of physical activity [33].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to emphasize that, according to the literature review, there are no reports focusing directly on the analysis of physical activity using IPAQ in the context of VR utilization among haemodialysis patients. Studies conducted in haemodialysis patient groups used IPAQ only to determine the relationship between the level of physical activity and the occurrence of sarcopenia [28], cognitive abilities [29], depression [30], cardiovascular disorders [31], and to compare the short version of the IPAQ with accelerometer-based physical activity measurement in haemodialysis patients [32], as well as to assess the plasma levels of 25-hydroxyvitamin D compared to the level of physical activity [33].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in accordance with another study using IPAQ on Greek older adults on hemodialysis, in the third year of the pandemic, which found that the majority of older persons presented inactivity (69.7%). Persons exhibiting moderate and high activity represented 28.8% and 1.5% of the sample, respectively [ 52 ]. Another study conducted in Greece during the COVID-19 pandemic, also using IPAQ, highlighted the insufficient level of older adults’ physical activity (low 44%, moderate 42.6 and high activity 13.4% [ 53 ].…”
Section: Discussionmentioning
confidence: 99%